Progressive damage assessment of centrally notched composite specimens in fatigue. (July 2015) - Aidi, Bilel; Philen, Michael K.; Case, Scott W.
Abstract: The aim of this study is to assess the residual properties and the corresponding damage states within centrally notched quasi-isotropic [0/−45/+45/90]S T650/F584 (Hexcel) carbon-fiber/epoxy composites subjected to fatigue loading using Digital Image Correlation (DIC), radiography, and a non-contact vibration measurement technique. Quasi-static tests were performed on virgin samples using DIC to determine the full-field in-plane strains at different applied load levels. Fatigue tests were interrupted during the fatigue lifetimes in order to perform quasi-static tests with DIC measurements. Non-contact vibration measurements were performed to investigate the effect of fatigue damage on residual frequency responses. X-ray computed tomography was used to determine the type, location, and extent of fatigue damage development. The results provide an important step in the validation of DIC and vibration response as a powerful combined non-destructive evaluation tool for monitoring the development of fatigue damage as well as predicting the damage level of notched composite materials.